2012
DOI: 10.1104/pp.112.196816
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of VQ Motif-Containing Proteins in Arabidopsis as Interacting Proteins of WRKY Transcription Factors    

Abstract: WRKY transcription factors are encoded by a large gene superfamily with a broad range of roles in plants. Recently, several groups have reported that proteins containing a short VQ (FxxxVQxLTG) motif interact with WRKY proteins. We have recently discovered that two VQ proteins from Arabidopsis (Arabidopsis thaliana), SIGMA FACTOR-INTERACTING PROTEIN1 and SIGMA FACTOR-INTERACTING PROTEIN2, act as coactivators of WRKY33 in plant defense by specifically recognizing the C-terminal WRKY domain and stimulating the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
411
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(458 citation statements)
references
References 60 publications
33
411
0
14
Order By: Relevance
“…A loss-of-function mutant harboring a transposon tag in vq8 displayed a pale-green and stunted growth phenotype throughout its life cycle (Cheng et al, 2012). It is likely that VQ8 regulates chloroplast development or photosystem assembly, consistent with its predicted localization to plastids.…”
Section: Vq Proteins In Plant Growth and Developmentmentioning
confidence: 91%
See 3 more Smart Citations
“…A loss-of-function mutant harboring a transposon tag in vq8 displayed a pale-green and stunted growth phenotype throughout its life cycle (Cheng et al, 2012). It is likely that VQ8 regulates chloroplast development or photosystem assembly, consistent with its predicted localization to plastids.…”
Section: Vq Proteins In Plant Growth and Developmentmentioning
confidence: 91%
“…In addition, VQ22 may interact with WRKY28 and WRKY51 to negatively control JA-mediated defense (Hu et al, 2013a). Two systematic yeast two-hybrid assays showed that a large proportion of VQ proteins associate physically with members of group I or group IIc WRKY transcription factors (Table I; Rushton et al, 2010;Cheng et al, 2012;Pecher et al, 2014). This interaction with WRKY members was further validated for VQ4 in Arabidopsis protoplasts .…”
Section: Mode Of Action Of Vq Proteinsmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, vQ proteins were reported to act as co-factors that positively or negatively regulate gene expression (Cheng et al 2012). Also, chromatin remodeling has also started to emerge as an important mode whereby the regulatory mechanism modulates expression of target gene expression during stress responses (Trivedi et al 2012;wang et al 2012a).…”
Section: Wrky Transcription Factors-domain Structure and Bindingmentioning
confidence: 99%